Oil palm biomass conversion to bio-oil through direct fired pyrolysis process - Ahmad Zulkhairi, Muhamad (2010)
The objectives of this study are to investigate the impact different biomasses,Empty Fruit Bunches(EFB)and Palm Kernel Shells(PKS),reaction temperature and air damper setting to the conversion of bio-oil and to determine the compatibility of direct fired reactor used in this system with the electric heated fired used in pyrolysis study worldwide.In this study,pyrolysis of EFB and PKS were investigated by using a direct heated pyrolysis reactor.The comparison of the conversion bio-oil obtained from this two different type of sample were studied.Since,a good EFB samples are very limited, the study of effect on reactor temperature and heating rate to the conversion of bio-oil was investigated by using PKS sample.The reaction temperature examined in this study was varied in the range of 300-500oC.Meanwhile, air damper setting in the range of 2.0-4.0 with a constant fuel setting at 19 mmbar were studied.In addition,the competiveness of the direct heated reactor also was investigated by making the comparison in term of percentage of bio-oil conversion with electric heated reactor used worldwide.For the conversion of bio-oil between EFB and PKS, PKS recorded higher yields of bio-oil compared to EFB.The highest conversions of bio-oil were gained at the reaction temperature of 400oC and air damper setting at 4 respectively.The study of the compatibility of direct fired reactor showed that the direct fired reactor was competitive since the conversion of bio-oil was in the range recorded by the electric heated reactor.This study concluded that the conversion of bio-oil was obtained by using PKS sample at the moderate reactor temperature and highest setting of air damper.This study also determined that the direct fired reactor able to become the new potential alternatives in the pyrolysis process since this kind of reactor is cost,energy and time effective compared to the electric heated reactor.